Geophilomorpha from Alborz Mountains and a checklist of Chilopoda from Iran - Zarei, Roghaieh; Rahimian, Hassan; Mirmonsef, Hassan; Bonato, Lucio (Zootaxa, 2020)
This study presents an updated checklist of centipedes (Chilopoda) from Iran based on a review of the literature and recently examined specimens of Geophilomorpha collected from many sites in the Alborz Mountains. The centipedes of Iran comprise 48 species, of which 17 species have so far only been reported from Iran. Many species are known from a single locality, and only from specimens of a single sex. Species of the geophilomorph genera Clinopodes and Strigamia are here reported from Iran for the first time. The checklist includes all published geographical distribution data from Iran and a comparison with the centipede fauna of neighboring countries using the Jaccard index. The Iranian centipede fauna is still scantily known and further investigations are expected to contribute substantially, especially because of the diverse physiography of the country.